Multimedia Workstations: Electronic Assistants for HealthCare Professionals - Degoulet, P.; Jean, F-C.; Safran, C. (Yearbook of Medical Informatics, 1996)
The increasing costs of health care and the economic reality has produced an interesting paradox for the health professional to perform more clinical work with fewer support personnel. Moreover, an explosion of the knowledge-base that underlies sound clinical care not only makes effective time management critical, but also knowledge management compelling. A multimedia workstation is an electronic assistant for the busy health professional that can help with administrative tasks and give access to clinical information and knowledge networks. The multimedia nature of processed information reflects an evolution of medical technologies that involve more and more complex objects such as video sequences or digitized signals. Analysis of the 445 Medline-indexed publications for the January 1991 to December 1994 period, that included the word “workstation” either in their title or in their abstract, helps in refining objectives and challenges both for health professionals and decision makers. From an engineering perspective, development of a workstation requires the integration into the same environments of tools to localize, access, manipulate and communicate the required information. The long-term goal is to establish an easy access in a collaborative working environment that gives the end-user the feeling of a single virtual health enterprise, driven by an integrated computer system when the information system relies on a set of heterogeneous and geographically distributed components. Consequences in terms of migration from traditional client/server architectures to more client/network architectures are considered.
Keywords: Health-care Professional Workstation; Software Engineering; Integration; Internet; Intranet